Analise da expressão dos genes de reparo da lesão de fita dupla do DNA de trabalhadores rurais expostos a agrotóxicos - Farias, Izabelle Rocha (2017)
The need to increase the demand for food produced brought with it an incorporation of technical-scientific development in agriculture and became a justification for the use of some chemicals in order to obtain a higher production through the manipulation of organic factors. The damage caused by high levels of toxicity of pesticides in a greater number of cases of cancers in farmers, making studies of the mechanisms of action involved and the damages that can cause human health of extreme relevance. In order to maintain a genomic integrity and its human stability around 150 genes involved in our DNA repair mechanisms. These errors when a DNA tape (DSBs) can be corrected by two types of mechanism, a Homologous Recombination (HR) and a Joint of Non-Homologous Extremities (NHEJ). Problems in DNA tape repair mechanisms in response to various types of damage caused by exposure to agrochemicals by farmers may trigger the accumulation of genetic genes and / or a deregulation of cell growth, leading to genomic instability and neoplastic development. The aim of the present study was to analyze genetic genetics by genetic cytogenetics by gene expression using the real-time PCR technique using ATM, BRCA1, BRCA2, XRCC5, XRCC6, RAD51 and LIG4 genes, belonging to the double-stranded DNA repair mechanism. This analysis was based on 90 cases of rural workers exposed to pesticides in the region of the Chapada do Apodi, in Limoeiro do Norte, and 10 samples from healthy individuals as control. With this study, it was possible to identify the ATM, LIG4 and XRCC5 genes presented the level of expression significant for a time variable of exposure to agrochemicals and for a variable groups of farmers, the genes LIG4, XRCC5 and XRCC6 presented the level of expression Para as variables Smoke and alcohol levels; expression levels of the XRCC5 and XRCC6 genes were still significant for a variable use of EPIs; the BRCA2 gene presented significance of expression for a variable karyotype; finally, gene XRCC6 a variable type of contact with pesticide. These results support the importance of ATM, BRCA1, BRCA2, XRCC5, XRCC6 and LIG4 genes in the maintenance of genomic stability, promoting a better understanding of the cellular mechanisms influenced by exposure to pesticides.